Do endometriomas grow during ovarian stimulation for assisted reproduction? A three-dimensional volume analysis before and after ovarian stimulation. Issue 2 (February 2018) - Seyhan, Ayse; Urman, Bulent; Turkgeldi, Engin; Ata, Baris
Abstract: Whether endometriomas grow because of supraphysiological oestradiol levels attained during ovarian stimulation for assisted reproduction techniques is a concern. In this prospective study, 25 women with 28 endometriomas underwent three-dimensional ultrasound using sono-automated volume calculation software. Endometrioma volume was measured on the first day of gonadotrophin injection (V1) and the day of ovulation trigger (V2). Nine (36%) women were stimulated in a gonadotrophin releasing hormone antagonist protocol (GnRH), 13 (52%) in a long, and three (12%) in an ultra-long GnRH agonist protocol. Mean duration of stimulation was 10.3 days with median total gonadotrophin dose of 4500 IU/day. Median number of cumulus oocyte complexes was five, and metaphase-two oocytes was four. None of the endometriomas were punctured during oocyte retrieval. Median V1 was 22.2 ml (12–30 ml) and median V2 was 24.99 ml (11.2–37.4 ml) with P = 0.001. Twenty-three out of 28 endometriomas (82%) grew to some extent during ovarian stimulation. Endometrioma growth was positively correlated with prestimulation cyst volume (Correlation coefficient 0.664; P < 0.01). Although the 3-ml average growth was statistically significant, it could be regarded as clinically insignificant.